Nitrogen-doped graphite-phase carbon nitride nanosheet loaded optical fiber composite photocatalytic material as well as preparation method and application thereof

By loading nitrogen-doped graphite phase carbon nitride nanosheets onto the optical fibers, the composite photocatalytic material is solved, and the existing photocatalytic materials are insufficient in water and difficult to recover catalysts is achieved, and the efficient degradation of harmful substances in wastewater and the recycling of materials is achieved.

CN119588431APending Publication Date: 2025-03-11SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510070369.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing photocatalytic materials are insufficient in water and are difficult to recover catalysts, resulting in low catalytic efficiency and high risk of secondary pollution.

Method used

The nanosheets are loaded onto the optical fiber composite photocatalytic material by using nitrogen-doped graphite phase carbon nitride nanosheets. The nanosheets are loaded onto the optical fibers through a simple preparation method to achieve continuous recycling and utilization of the material.

Benefits of technology

It improves photocatalytic activity and stability, achieves the degradation efficiency of hazardous substances in more than 90% of wastewater, and can be reused more than three times, solving the problem of difficulty in catalyst recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588431A_ABST
    Figure CN119588431A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped graphite phase carbon nitride nanosheet loaded optical fiber composite photocatalytic material as well as a preparation method and application thereof. The nitrogen-doped graphite phase carbon nitride nanosheet is composed of C and N elements, and the constituent elements are uniformly dispersed on the surface of the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet, so that the nanosheet has a higher specific surface area and more surface active sites. The prepared nitrogen-doped graphite-phase carbon nitride nanosheet is loaded on the light-guide fiber, so that harmful substances in wastewater can be degraded in a short time, the nanosheet can be repeatedly used for more than three times, and the nanosheet is simple to use, green and environment-friendly. The preparation method of the nitrogen-doped graphite-phase carbon nitride nanosheet or the method of loading the nitrogen-doped graphite-phase carbon nitride nanosheet on the light-guide fiber is simple to operate and wide in raw material source, and has certain practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field and application field of photocatalysts, and in particular to a nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] With the acceleration of my country's industrialization and urbanization, the problem of urban river and lake water pollution has become increasingly prominent. Traditional environmental remediation technologies have gradually failed to meet people's requirements. Therefore, finding a new type of efficient and energy-saving environmental remediation technology has become one of the current hot research directions. At present, the methods for removing antibiotics from water mainly include physical adsorption, oxidative degradation, biodegradation, membrane separation, catalytic degradation, etc. However, all of the above methods have problems such as low degradation efficiency, complex treatment process, high cost of consumables, difficulty in recovering catalysts, and high risk of secondary pollution to varying degrees.

[0003] Photocatalysis is a pollutant treatment method that converts light energy into chemical energy through photocatalysts, using hydroxyl radicals, superoxide radicals, singlet oxygen, etc. as reactive species to achieve oxidative decomposition of pollutants. Graphitic Carbon Nitride (g-C3N4) is a new type of nitrogen-doped carbon material that has attracted widespread attention due to its wide application potential in catalysis, optoelectronics, energy storage and other fields. Its structure is similar to graphite, but its composition contains nitrogen, which gives it some unique advantages in photocatalytic performance. Compared with other photocatalysts, its advantages are very prominent: it can absorb visible light, has good thermal and chemical stability, excellent electrical properties, is inexpensive and non-toxic, has abundant sources, and has a simple preparation and molding process. However, carbon nitride has the disadvantages of small surface area, weak light absorption, and poor charge separation efficiency. Its photocatalytic efficiency is still limited by its low specific surface area, which limits its further development. However, photocatalytic materials are generally micro-nanoscale, which makes it difficult to recover the catalyst, and the residual catalyst causes secondary pollution to the water body. In addition, photocatalysts are not stable enough in water and are prone to physical structural damage in water, which leads to poor performance of the catalyst over multiple cycles.

[0004] Therefore, developing a new type of photocatalytic material using graphite phase carbon nitride that can be used stably in water has become an urgent problem to be solved by many researchers. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing nitrogen-doped graphite-phase carbon nitride nanosheets with high photocatalytic activity and good stability, and a method for loading the nitrogen-doped graphite-phase carbon nitride nanosheets on the surface of optical fibers for continuous recycling. The process for preparing nitrogen-doped graphite-phase carbon nitride nanosheets is simple, the raw materials are wide and the cost is low, which meets the actual production needs and has great industrial application potential in semiconductor catalyst materials, water treatment and degradation of organic matter, etc.

[0006] Another object of the present invention is to use the above-mentioned material in the photocatalytic degradation of tetracycline hydrochloride, phenol and p-nitrophenol.

[0007] To achieve the above object, the present invention adopts the following technical solution: The preparation method of nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material comprises the following steps: S101, placing a nitrogen-containing compound and citric acid monohydrate into a ceramic crucible, and then placing the crucible in a muffle furnace for heating treatment; S102, taking out the ceramic crucible, cooling it naturally to obtain bulk nitrogen-doped graphite phase carbon nitride, and repeatedly washing the bulk nitrogen-doped graphite phase carbon nitride with deionized water and anhydrous ethanol; S103, grinding the bulk nitrogen-doped graphite phase carbon nitride washed in S102, placing it in a ceramic crucible again for heating treatment, and naturally cooling it to room temperature to obtain ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets; S104, loading the ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets on an optical fiber to obtain a nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material.

[0008] Preferably, the nitrogen-containing compound in step S101 is at least one of urea, biuret, and ammonium oxalate; Preferably, the mass ratio of the nitrogen-containing compound to citric acid monohydrate in step S101 is 900:1-1000:1; Preferably, the temperature increase treatment in step S101 is to increase the temperature from room temperature to 550-560° C. at a heating rate of 2-4° C. / min in natural air, and calcine at this temperature for 4-6 hours; Preferably, the temperature increase treatment in step S103 is to increase the temperature from room temperature to 400-500° C. at a temperature increase rate of 5° C. / min in natural air, and calcine at this temperature for 2-3 hours.

[0009] Preferably, the ultra-thin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets obtained in step S103 have a thickness of 0.72-2.3 nm.

[0010] As a further solution of the present invention, the loading method in step S104 includes the following steps: S201, weighing a certain amount of ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheet solid into distilled water, placing it in an ultrasonic reactor for ultrasonic reaction for 6-8 hours, and then centrifuging the obtained solution to remove large impurities to obtain an ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheet solution; S202, immersing the optical fiber in a solution of ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets, and after a certain reaction time, rinsing the optical fiber with deionized water, and drying to obtain a nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material.

[0011] Preferably, the centrifugal speed in step S201 is 4000-4300 rpm / min; Preferably, the reaction time in step S202 is 4-10 h, the drying temperature is 60-70° C., and the drying time is 10-12 h.

[0012] A nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material prepared by the method.

[0013] The present invention also provides an application of the nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material prepared by the above method in degrading harmful substances in wastewater, which specifically includes the following steps: placing the nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material in wastewater containing harmful substances for magnetic stirring, and recovering the photocatalytic material after the photocatalytic reaction is completed.

[0014] In the above application, preferably, the harmful substance includes antibiotics or phenol or p-nitrophenol; In the above application, preferably, the amount of the nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material added is 0.2-0.6 grams of ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheet per liter of wastewater; The antibiotic in the antibiotic wastewater is tetracycline hydrochloride; the initial concentration of the antibiotic in the antibiotic wastewater is 20-30 mg / L; The initial concentration of the phenol is 10 mg / L; the initial concentration of the p-nitrophenol is 10 mg / L; The photocatalytic reaction time is 45-80 minutes.

[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects: The present invention provides a nitrogen-doped graphite phase carbon nitride nanosheet, the surface of which is smoother, the curled edges of the surface are fewer and fewer, the porous structure can be clearly observed, it has a higher specific surface area, more surface active sites, and exhibits the characteristics of nano-confinement effect. Through the elemental analysis function attached to the transmission electron microscope, it was found that the nanosheet is composed of C and N elements, and the constituent elements are evenly dispersed on the surface of the ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet (500 ℃), and the catalytic efficiency is higher.

[0016] The present invention also provides a nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material, which has excellent stability and recyclability, can achieve photocatalytic degradation of more than 90% in wastewater within 30 minutes, and can be reused more than three times. It is simple to use and green and environmentally friendly, which not only solves the technical problem of the difficulty in recycling carbon nitride nanosheets in wastewater in the prior art, but also ensures the catalytic efficiency.

[0017] The present invention provides a method for preparing nitrogen-doped graphite phase carbon nitride nanosheets and a photocatalytic material. The whole process has simple steps and low requirements on equipment. The raw materials used are all common and cheap chemicals, which are safe and low in cost. The present invention also provides a corresponding method for photocatalytic degradation of antibiotics. The photocatalytic material has the advantages of fast catalytic degradation rate of tetracycline hydrochloride, high activity, good stability, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram and physical picture of the atomic structure of bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheet UNCN-500 (Note: blue represents N atoms and gray represents C atoms); Figure 2 Transmission electron microscope images of bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-400, UNCN-450, and UNCN-500; Figure 3 Detailed (ac) microscopic morphology of ultrathin mesoporous nitrogen-doped graphene-phase carbon nitride nanosheets (500 °C) and their corresponding (df) element distribution maps; Figure 4 Atomic force microscope images of bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-400, UNCN-450, and UNCN-500 (Note: the built-in images are the corresponding height images); Figure 5The test results of the photocatalytic activity of the photocatalytic materials prepared by bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-400, UNCN-450, and UNCN-500 for degradation of tetracycline hydrochloride under visible light; Figure 6 The test results of the photocatalytic activity of photocatalytic materials prepared by bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-500 for degradation of phenol under visible light; Figure 7 The test results of the reusability of ultra-thin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-500 loaded with optical fiber composite photocatalytic materials; Figure 8 The results show the photocatalytic activity of ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-500 loaded with optical fiber composite photocatalytic materials under different single wavelengths of visible light irradiation. DETAILED DESCRIPTION

[0019] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0020] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art. Example

[0021] Preparation of nitrogen-doped graphite phase carbon nitride nanosheets UNCN-500: A mixture of urea and citric acid monohydrate (the mass ratio of urea and citric acid monohydrate is 1 g: 1 mg) is placed in a ceramic crucible with a lid, which is placed in a muffle furnace, and then heated from room temperature to 550 °C in air at a heating rate of 2 °C / min, and maintained at this temperature for 4 hours, and then naturally cooled to room temperature to obtain bulk nitrogen-doped graphite phase carbon nitride NCN. The obtained bulk nitrogen-doped graphite phase carbon nitride NCN is repeatedly washed with deionized water and anhydrous ethanol.

[0022] The ground bulk nitrogen-doped graphite carbon nitride NCN was placed in an open ceramic crucible container, heated to 500 °C (etching temperature) at a heating rate of 5 °C / min at room temperature, and maintained at this temperature for 2 h. After cooling to room temperature, the sample was taken out to obtain ultra-thin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-500. Example

[0023] Preparation of nitrogen-doped graphite phase carbon nitride nanosheets UNCN-450: A mixture of urea and citric acid monohydrate (the mass ratio of urea and citric acid monohydrate is 1 g: 1 mg) is placed in a ceramic crucible with a lid, which is placed in a muffle furnace, and then heated from room temperature to 550 °C in air at a heating rate of 2 °C / min, and maintained at this temperature for 4 hours, and then naturally cooled to room temperature to obtain bulk nitrogen-doped graphite phase carbon nitride NCN. The obtained bulk nitrogen-doped graphite phase carbon nitride NCN is repeatedly washed with deionized water and anhydrous ethanol.

[0024] The ground bulk nitrogen-doped graphite carbon nitride NCN was placed in an open ceramic crucible container, heated to 450 °C (etching temperature) at a heating rate of 5 °C / min at room temperature, and maintained at this temperature for 2 h. After cooling to room temperature, the sample was taken out to obtain ultra-thin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-450. Example

[0025] Preparation of nitrogen-doped graphite phase carbon nitride nanosheets UNCN-400: A mixture of urea and citric acid monohydrate (the mass ratio of urea and citric acid monohydrate is 1 g: 1 mg) is placed in a ceramic crucible with a lid, which is placed in a muffle furnace, and then heated from room temperature to 550 °C in air at a heating rate of 2 °C / min, and maintained at this temperature for 4 hours, and then naturally cooled to room temperature to obtain bulk nitrogen-doped graphite phase carbon nitride NCN. The obtained bulk nitrogen-doped graphite phase carbon nitride NCN is repeatedly washed with deionized water and anhydrous ethanol.

[0026] The ground bulk nitrogen-doped graphite carbon nitride NCN was placed in an open ceramic crucible container, heated to 400 °C (etching temperature) at a heating rate of 5 °C / min at room temperature, and maintained at this temperature for 2 h. After cooling to room temperature, the sample was taken out to obtain ultra-thin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-400.

[0027] Material Characterization Data: The structural schematic diagram of bulk nitrogen-doped graphite carbon nitride NCN and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-500 was simulated by theoretical calculation, as shown in Figure 1 (a) and Figure 1 (b). Figure 1As can be seen in (a), the bulk nitrogen-doped graphite phase carbon nitride is a multilayer tri-iso-triazine ring structure, with the layers connected by van der Waals forces. When the bulk nitrogen-doped graphite phase carbon nitride is exfoliated by thermal oxidation at 500 °C, the hydrogen-bonded strands (especially the short hydrogen bonds) of the polymer melon units in the layers are not stable enough to the oxidation process in the air (or are reactive to the oxidation process in the air), and will gradually be oxidized, thereby reducing the thickness of the nitrogen-doped graphite phase carbon nitride flakes. Figure 1 (c) and Figure 1 As can be seen in (d), the volume of the same mass of ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets is significantly larger than the volume of bulk nitrogen-doped graphite phase carbon nitride, which indicates that after thermal oxidation exfoliation, the appearance of the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets is fluffy.

[0028] Transmission electron microscopy was used to observe the morphological evolution of NCN, UNCN-500, UNCN-450, and UNCN-400 at different temperatures. Figure 2 shown. Figure 2 (a) is the microscopic morphology of bulk nitrogen-doped graphite phase carbon nitride. It can be seen from the figure that bulk nitrogen-doped graphite phase carbon nitride is a multilayered flake structure with a porous morphology and many curled areas on the surface of the flake structure. Figure 2 (b) and Figure 2 (c) The microstructures of ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets (400°C) and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets (450°C), respectively. It can be seen from the figure that compared with the microstructure of bulk nitrogen-doped graphite carbon nitride, the curling area on the surface of the microstructure of ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets (400°C) and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets (450°C) is reduced and the curling area begins to spread, which indicates that after thermal oxidation etching at 400°C and 450°C, the number of multilayer nitrogen-doped graphite carbon nitride layers gradually decreases, but this temperature does not etch the multilayer nitrogen-doped graphite carbon nitride into the state of ultrathin nanosheets. However, when the thermal oxidation etching temperature reaches 500°C, the nitrogen-doped graphite carbon nitride has become an ultrathin nanosheet, as shown in Figure 2. Figure 2 As shown in (d), compared with the morphology of multilayer nitrogen-doped graphitic carbon nitride, the surface of ultrathin mesoporous nitrogen-doped graphitic carbon nitride nanosheets (500°C) becomes smoother, the curled edges of the surface become less and less, and the porous structure can be clearly observed.

[0029] High-magnification TEM images were used to further observe the morphology of UNCN-500. Figure 3(a) It can be seen that the ultrathin mesoporous nitrogen-doped graphene-phase carbon nitride nanosheets (500°C) are almost transparent, indicating that they are extremely thin, which intuitively illustrates the ultrathin nanosheet size of the ultrathin mesoporous nitrogen-doped graphene-phase carbon nitride nanosheets (500°C). Figure 3 The high-resolution TEM image in (b) clearly shows that the surface of the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet (500°C) has a distinct pore structure, which indicates that the pore structure of the nitrogen-doped graphite phase carbon nitride after thermal oxidation exfoliation is more obvious. In addition, studies have shown that the smaller the pore size, the larger the specific surface area and the more surface active sites. In addition, we also tested the element distribution of the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet (500°C) by the elemental analysis function attached to the transmission electron microscope, such as Figure 3 (df). Figure 3 (e) and Figure 3 As can be seen in (f), the mapping distribution of carbon and nitrogen elements in ultrathin mesoporous nitrogen-doped graphene carbon nitride nanosheets (500 ℃) is similar to that in Figure 3 (d) is consistent with the TEM image. This shows that the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets (500 ℃) are composed of C and N elements, and the constituent elements are uniformly dispersed on the surface of the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets (500 ℃).

[0030] from Figure 4 As can be seen in (a), the flake thickness of bulk nitrogen-doped graphite phase carbon nitride is 4.7 nm. However, when bulk nitrogen-doped graphite phase carbon nitride is thermally oxidized at 400 °C, its thickness does not change significantly, as shown in Figure 2. Figure 4 (d) When the temperature rises to 450 °C, the thickness of the nitrogen-doped graphite-phase carbon nitride nanosheets decreases to 2.3 nm, as shown in Figure 4 As shown in (c), as the temperature continues to rise to 500°C, the thickness of the nitrogen-doped graphene-phase carbon nitride nanosheets decreases to 0.72nm, which is only the thickness of 2-3 layers of CN basic units. Figure 4 As shown in (b), it can be seen that the surface of the ultra-thin nitrogen-doped graphene phase carbon nitride nanosheet (500 °C) has a porous structure. This result is consistent with what is seen in the TEM image, which shows that the hydrogen bonds react completely at the appropriate temperature to achieve the result of ultra-thin nanosheets. Example

[0031] The prepared ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet UNCN-500 is loaded on the optical fiber: 0.3 g of ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet UNCN-500 is weighed in a beaker, distilled water is added, the beaker is placed in an ultrasonic reactor for ultrasonic reaction for 8 hours, the centrifugal speed is adjusted to 4000 rpm to centrifuge and remove large impurities to obtain an ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet UNCN-500 solution. The optical fiber is immersed in the solution for 6 hours to react, so that the ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet UNCN-500 is loaded on the surface of the optical fiber, and the optical fiber is taken out and dried at 60°C for 12 hours to obtain a nitrogen-doped graphite phase carbon nitride nanosheet loaded optical fiber composite photocatalytic material. Example

[0032] The photocatalytic material prepared in Example 4 was placed in a photocatalytic reaction device, and wastewater containing 20 mg / L tetracycline hydrochloride was added. The magnetic stirrer was turned on, and the photocatalytic reaction was carried out using visible light for 90 minutes to complete the photocatalytic degradation of tetracycline hydrochloride in the wastewater. The sampling time for judging the degree of the photocatalytic reaction was 0, 5, 10, 15, 20, 30, 40, 50, and 60 minutes during the reaction, and the concentration of tetracycline hydrochloride in the solution was measured. Time T was used as the horizontal coordinate, and C / C0 was used as the vertical coordinate (where C0 was the concentration of tetracycline hydrochloride at the initial time of time 0).

[0033] For comparison, bulk nitrogen-doped graphite carbon nitride and ultrathin mesoporous nitrogen-doped graphite carbon nitride nanosheets UNCN-400 and UNCN-450 were loaded on optical fibers using the above method to conduct photocatalytic effect experiments. In addition, a group of controls without adding light sources were set up. The experimental results are as follows: Figure 5 shown.

[0034] from Figure 5It can be seen that in the absence of light source, the photodegradation efficiency did not change significantly after 30 minutes of magnetic stirring, which indicates that the photocatalysis has reached adsorption-desorption equilibrium, which also shows that light plays an important role in the photocatalytic degradation reaction. The 30 minutes of magnetic stirring of the photocatalytic degradation system before illumination indirectly proves the adsorption capacity of the photocatalyst. From the curve in the figure, it can be seen that the adsorption capacity of the bulk nitrogen-doped graphite phase carbon nitride and the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets UNCN-400, UNCN-450, and UNCN-500 are similar. And the photocatalytic degradation efficiency of tetracycline hydrochloride prepared by ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets UNCN-400, UNCN-450, and UNCN-500 is higher than that of bulk nitrogen-doped graphite phase carbon nitride. In addition, the photocatalytic efficiency of ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets (500 ℃) can reach 92% within 20 minutes, while the photocatalytic efficiency of bulk nitrogen-doped graphite phase carbon nitride is 42%. When the light irradiation time reaches 60 min, the photocatalytic efficiency of ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets (500 ℃) can reach 100%.

[0035] The same method was used to test the removal efficiency of phenol by photocatalytic materials made of UNCN-500 nanosheets and bulk NCN. The experimental conditions were 0.5 g / L catalyst and 10 mg / L phenol. The results are as follows: Figure 6 As shown, UNCN-500 can remove 99% of phenol after 180 minutes, NCN can remove 59% of phenol after 180 minutes, and doped CN can remove 11% of phenol after 180 minutes. The present invention improves the removal rate of phenol by 9 times.

[0036] The same method was used to test the removal efficiency of p-nitrophenol by the photocatalytic material made of UNCN-500 nanosheets. The experimental conditions were 0.5 g / L catalyst, 5 mg / L or 10 mg / L p-nitrophenol. The results showed that the catalyst of the present invention had a high removal rate for the difficult-to-degrade polluted p-nitrophenol. Example

[0037] The nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material prepared in Example 4 was tested three times in succession according to the photocatalytic degradation steps of Example 4 to test its reusability. The results are as follows: Figure 7 As shown, the prepared photocatalytic material photocatalytically degraded tetracycline hydrochloride in wastewater three times in a row, and the degradation efficiency of the second and third times was above 90%. Example

[0038] The single wavelength of visible light was adjusted to 420 nm, 475 nm and 550 nm, and the nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material prepared in Example 4 was tested according to the photocatalytic degradation steps of Example 4. The results are as follows: Figure 8 As shown, at visible light wavelengths of 420nm and 475nm, the efficiency of the photocatalytic material in degrading tetracycline hydrochloride was above 80%, while at a visible light wavelength of 550nm, the efficiency of the photocatalytic material in degrading tetracycline hydrochloride dropped to 52.2%, indicating that the present invention has excellent visible light response capability, a wide range of light energy utilization, and great practical application potential.

[0039] In order to further test the actual degradation efficiency of the photocatalytic material made of the UNCN-500 nanosheets of the present invention in a sewage environment, when humic acid, NaCl, and Na2CO3 were added to the sewage respectively, the antibiotic removal efficiency could still reach 90%, showing excellent ability to resist complex water conditions.

[0040] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material, characterized in that: An optical fiber is used as a carrier, and ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets are loaded on the optical fiber; The ultra-thin mesoporous nitrogen-doped graphite phase carbon nitride nanosheet has a thickness of 0.72-2.3 nm; The method for loading ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets on optical fibers is as follows: S101, weighing a certain amount of ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheet solid into distilled water, placing the solid in an ultrasonic reactor for ultrasonic reaction for 6-8 hours, and then centrifuging the resulting solution to remove large impurities, thereby obtaining an ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheet solution; S102, immersing the optical fiber in a solution of ultrathin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets, and after a certain reaction time, rinsing the optical fiber with deionized water, and drying to obtain a nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material.

2. The nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material according to claim 1, characterized in that: The centrifugal speed in step S101 is 4000-4300 rpm / min; the reaction time in step S102 is 4-10 hours, the drying temperature is 60-70° C., and the drying time is 10-12 hours.

3. The nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material according to claim 1, characterized in that: The method for preparing the ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets comprises the following steps: S201, placing a nitrogen-containing compound and citric acid monohydrate into a ceramic crucible, and then placing the crucible in a muffle furnace for heating treatment; S202, taking out the ceramic crucible, cooling it naturally to obtain bulk nitrogen-doped graphite phase carbon nitride, and repeatedly washing the bulk nitrogen-doped graphite phase carbon nitride with deionized water and anhydrous ethanol; S203, grinding the bulk nitrogen-doped graphite phase carbon nitride washed in S202, placing it in a ceramic crucible again for heating treatment, and naturally cooling it to room temperature to obtain ultrathin mesoporous nitrogen-doped graphite phase carbon nitride nanosheets.

4. The nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material according to claim 3, characterized in that: The mass ratio of the nitrogen-containing compound to citric acid monohydrate in step S201 is 900:1-1000:

1.

5. The nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material according to claim 3, characterized in that: The nitrogen-containing compound in step S201 is at least one of urea, biuret, and ammonium oxalate.

6. The nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material according to claim 3, characterized in that: The temperature increase treatment in step S203 is to increase the temperature from room temperature to 400-500° C. at a heating rate of 5° C. / min in natural air, and calcine at this temperature for 2-3 hours.

7. Use of the nitrogen-doped graphite-phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material in degrading harmful substances in wastewater as claimed in any one of claims 1 to 2, characterized in that: The nitrogen-doped graphite phase carbon nitride nanosheet-loaded optical fiber composite photocatalytic material is placed in wastewater containing harmful substances for magnetic stirring, and the photocatalytic material is recovered after the photocatalytic reaction is completed.

8. The use according to claim 7, characterized in that: The harmful substances include antibiotics or phenol or p-nitrophenol.

9. The use according to claim 7, characterized in that: 0.2-0.6 g / L of ultra-thin mesoporous nitrogen-doped graphite-phase carbon nitride nanosheets is added to the wastewater.

10. The use according to claim 7, characterized in that: The photocatalytic reaction time is 45-80 minutes.